Process evaluation of the Albany Physical Activity and Nutrition (APAN) program, a home‐based intervention for metabolic syndrome and associated chronic disease risk in rural Australian adults. (14th July 2016) - Blackford, Krysten; Lee, Andy; James, Anthony P.; Waddell, Tracy; Hills, Andrew P.; Anderson, Annie S.; Howat, Peter; Jancey, Jonine
Abstract : Issue addressed: The Albany Physical Activity and Nutrition (APAN) study investigated the effects of the APAN program, a home‐based intervention on dietary and physical activity behaviours and chronic disease risk for rural Australian adults. This paper reports on the process evaluation to gain insight into the link between intervention elements and outcomes. Methods: The APAN program comprised resources to improve participants' diet and physical activity. Printed and online resources were provided to participants, complemented by motivational interviews via telephone. Process evaluation used mixed‐methods, with a sample of 201 intervention participants residing in a disadvantaged rural area. Participants were aged 50 to 69 years with, or at risk of, metabolic syndrome. Quantitative data were collected using an online survey (n = 73); qualitative data were collected via telephone exit interviews with intervention completers (n = 8) and non‐completers (n = 8), and recruitment notes recorded by research assistants. Results: The attrition rate of the program was 18%; major reasons for withdrawal were health and personal issues and a loss of interest. The majority of participants found the printed resources useful, attractive, and suitable to their age group. The website was the least preferred resource. Reasons for completing the program included the desired health benefits, wanting to honour the commitment, and wanting to assist with research. Conclusions: Carefully planned recruitment will reduce the burden on resources and improve uptake. Understanding reasons for attrition such as family or personal barriers and health issues will assist practitioners to support participants overcome these barriers. Given participants' preference for printed resources, and the known effectiveness of these in combination with other strategies, investigating methods to encourage use of telephone and online support should be a priority. So what?: This process evaluation provided an overview of recruitment challenges and preferred intervention components. It is desirable that future work determines the most effective intervention components for rural adults at risk of chronic disease. Abstract : This paper reports on the process evaluation of the Albany Physical Activity and Nutrition program, which aimed to improve the diet and physical activity of rural adults at risk of chronic disease. Health promotion practitioners planning and implementing similar interventions may learn from these findings, particularly for recruitment and retention of participants.